PENGARUH CASH FLOW, NET WORKING CAPITAL, FIRM SIZE, DAN LEVERAGE TERHADAP CASH HOLDING - Sukma Dwi Yanti; Muhammad Taufik Azis; Imam Hadiwibowo (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
Cash Holding has an important role for every company to determine the level of company liquidity. This study aims to determine the effect of Cash Flow, Net working Capital, Firm Size, and Leverage on Cash Holding. Empirical study of this research on consumer goods industrial sector companies listed on the Indonesia Stock Exchange. The research period used is 2017-2021. The sample was selected by purposive sampling method. Based on the existing criteria, 34 companies became the research sample. The data used in this study is secondary data, namely audited financial statements obtained from the website www.idx.co.id. The method used in this study is a quantitative method. The data analysis technique used is multiple linear regression analysis using SPSS software version 20. The results of this study prove that Cash Flow and Net Working Capital can be used as a reference that has a positive impact on Cash Holding, while Firm Size and Leverage have no impact on Cash Holding Company.